2021
DOI: 10.3390/nu13030930
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Changes and Determinants of Children’s and Adolescents’ Body Weight Increase during the First COVID-19 Lockdown in Greece: The COV-EAT Study

Abstract: Previous studies showed that the coronavirus disease 2019 (COVID-19) lockdown imposed changes in adults’ lifestyle behaviors; however, there is limited information regarding the effects on youth. The COV-EAT study aimed to report changes in children’s and adolescents’ lifestyle habits during the first COVID-19 lockdown and explore potential associations between changes of participants’ lifestyle behaviors and body weight. An online survey among 397 children/adolescents and their parents across 63 municipalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
219
5
20

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(270 citation statements)
references
References 34 publications
26
219
5
20
Order By: Relevance
“…In addition, almost half of the respondents reported unhealthy eating habits in children. Despite the short-term nature of the current study to make conclusions, this finding is consistent with that of Androutsos et al, who reported an increase of body weight by 35% of children/adolescents during the first COVID-19 lockdown in Greece associated with increased consumption of breakfast, salty snacks, and total snacks, and with decreased physical activity [ 37 ]. According to parents, children adopted unhealthy eating habits while staying at home.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, almost half of the respondents reported unhealthy eating habits in children. Despite the short-term nature of the current study to make conclusions, this finding is consistent with that of Androutsos et al, who reported an increase of body weight by 35% of children/adolescents during the first COVID-19 lockdown in Greece associated with increased consumption of breakfast, salty snacks, and total snacks, and with decreased physical activity [ 37 ]. According to parents, children adopted unhealthy eating habits while staying at home.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, increased sedentary time is likely due to a combination of boredom, free time, distance learning and online social activity. 31 In the present study, exercise volume was associated with weight change in women alone, possibly due to the low exercise volume both before and during the lockdown, far below the ACSM-recommended exercise volume (16.7 MET-hours/week), 15 and the change in exercise volume in the overall population being small. Various studies have looked into physical activity.…”
Section: Discussioncontrasting
confidence: 53%
“…These findings are consistent with prior research showing sedentary behaviour, TV viewing and computer use being risk factors for the increased weight 29 30 and consistent with similar observations in Europe. 31 A possible reason behind this may be due to the general restraint to one's home and the greater availability of free time without requiring active travel to school/work. In addition, increased sedentary time is likely due to a combination of boredom, free time, distance learning and online social activity.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, such preventive measures caused significant changes of lifestyle and dietary habits, with potential influence on metabolic health in the general population. In particular, a weight gain was often reported both in children 27,28 and in adults 29‐32 . A recent systematic review found that the social containment measures due to the COVID‐19 lockdown generated a weight gain in 7.2%‐72.4% of subjects 31 …”
Section: Discussionmentioning
confidence: 99%